Spain : Financial Sector Assessment Program-Technical Note-Supervision of Spanish Banks. (IMF Staff Country Reports; Country Report, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program (FSAP) for Spain in the area of banking supervision. Banking regulation and supervision of Spanish banks have improved considerably since the 2012 FSAP. Swift and determined action addressed the major weaknesses that led to the accumulation of imbalances in the banking system in the period leading to the crisis. Further reforms are needed because the transformation of the banking supervision function is far from complete. Actions to address misclassification and underprovisioning of assets have shown very good progress, but oversight must continue.